2006
DOI: 10.1016/j.cell.2005.10.036
|View full text |Cite|
|
Sign up to set email alerts
|

VEGF-Induced Adult Neovascularization: Recruitment, Retention, and Role of Accessory Cells

Abstract: Adult neovascularization relies on the recruitment of circulating cells, but their angiogenic roles and recruitment mechanisms are unclear. We show that the endothelial growth factor VEGF is sufficient for organ homing of circulating mononuclear myeloid cells and is required for their perivascular positioning and retention. Recruited bone marrow-derived circulating cells (RBCCs) summoned by VEGF serve a function distinct from endothelial progenitor cells. Retention of RBCCs in close proximity to angiogenic ves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

32
697
2
16

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 1,076 publications
(760 citation statements)
references
References 40 publications
32
697
2
16
Order By: Relevance
“…Our results suggest that a similar process can also occur independently of tumor with drug-induced up-regulation of multiple proangiogenic growth factors. In this regard, a number of studies have shown that angiogenesis can be induced or amplified by G-CSF (18), SCF (19), SDF-1␣ (20), and osteopontin (21), by diverse mechanisms, including mobilization of circulating bone-marrow-derived proangiogenic cell populations (22), such as endothelial progenitor cells (23). Such effects could conceivably contribute to the rapid vascular ''rebound'' in mouse tumors observed within 1 week of terminating therapy with an RTKI similar in nature to sunitinib (16), results that could clearly have implications for whether a continuous vs. discontinuous schedule of treatment using such drugs would be superior.…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggest that a similar process can also occur independently of tumor with drug-induced up-regulation of multiple proangiogenic growth factors. In this regard, a number of studies have shown that angiogenesis can be induced or amplified by G-CSF (18), SCF (19), SDF-1␣ (20), and osteopontin (21), by diverse mechanisms, including mobilization of circulating bone-marrow-derived proangiogenic cell populations (22), such as endothelial progenitor cells (23). Such effects could conceivably contribute to the rapid vascular ''rebound'' in mouse tumors observed within 1 week of terminating therapy with an RTKI similar in nature to sunitinib (16), results that could clearly have implications for whether a continuous vs. discontinuous schedule of treatment using such drugs would be superior.…”
Section: Discussionmentioning
confidence: 99%
“…CXCL12 and VEGF are also suggested to act as chemoattractants for myeloid cells [222,223] and may act in concert for recruiting neutrophil to the tumor microenvironment. Under normal conditions, a tight cooperation between myeloid cells and endothelial progenitor cells is required for proper neovascularization [223].…”
Section: Neutrophil Recruitment To the Tumor Microenvironmentmentioning
confidence: 99%
“…Under normal conditions, a tight cooperation between myeloid cells and endothelial progenitor cells is required for proper neovascularization [223]. VEGF induces bone marrow-derived myeloid cell mobilization to the circulation and through VEGF-mediated upregulation of SDF1/CXCL12 in activated perivascular myofibroblasts, the myeloid cells are kept in close proximity to angiogenic vessels [223]. VEGF is upregulated in a wide variety of tumors [69,[224][225][226][227], as is CXCL12 [228].…”
Section: Neutrophil Recruitment To the Tumor Microenvironmentmentioning
confidence: 99%
See 1 more Smart Citation
“…To this end, there seem to exist multiple schools of thought. One suggests that bone marrow-derived hematopoietic cells home to areas of vascular injury and settle in close approximation to the newly forming vasculature, contributing to angiogenesis via secretion of important cytokines for endothelial proliferation and recruitment (18,19). A second proposes that bone marrow-derived endothelial progenitor cells (EPCs), the definition of which remains elusive (20), are able to directly participate in angiogenesis (21,22 (Fig.…”
Section: Who Gives Rise To Whom?mentioning
confidence: 99%